(3xy2 – y)dx – (2x²y– xy²)dy = 0
Answers
Answered by
1
Step-by-step explanation:
(3xy² - y³) dx - (2x²y - xy²) dy = 0
⇒ dy/dx = (3xy² - y³)/(2x²y - xy²) ...(i)
Let us take,
y = vx
Then,
dy/dx = v + x (dv/dx)
From (i), we get
v + x (dv/dx) = (3x v²x² - v³x³)/(2x² vx - x v²x²)
⇒ v + x (dv/dx) = (3v² - v³)/(2v - v²)
⇒ x (dv/dx) = (3v - v²)/(2 - v) - v
⇒ x (dv/dx) = (3v - v² - 2v + v²)/(2 - v)
⇒ x (dv/dx) = v/(2 - v)
⇒ {(2 - v)/v} dv = (dx)/x
⇒ 2 (dv)/v - dv = (dx)/x
∴ integrating we get
2 ∫ (dv)/v - ∫ dv = ∫ (dx)/x
⇒ 2 logv - v = logx + c, where c is intergral constant
⇒ 2 log (y/x) - (y/x) = logx + c [ ∵ y = vx ]
⇒ 2 logy - 2 logx - (y/x) = logx + c
⇒ 2 logy - 3 logx = (y/x) + c,
which is the required primitive
Similar questions